36. Advanced Accessibility Features for Inclusive Distance Education - Matula Schwartz, Linda (International Review of Research in Open and Distributed Learning, 2004)
Report #32 in this series has considered the special attention required to make online collaborative tools fully accessible. The particular challenge for software developers is to optimize the accessibility of online education for persons with disabilities. In the process, the software's efficiency for all users is likely to be increased. The current paper expands on Report #32, by the same author, in reviewing specific software products that are rising to the online accessibility challenge: Allen eC, iCommunicator, and OpenCampus.